Allergen-Specific Antibodies Regulate Secondary Allergen-Specific Immune Responses - Eckl-Dorna, Julia; Villazala-Merino, Sergio; Linhart, Birgit; Karaulov, Alexander V.; Zhernov, Yury; Khaitov, Musa; Niederberger-Leppin, Verena; Valenta, Rudolf (Frontiers in Immunology, 2019)
Immunoglobulin E (IgE)-associated allergy is the most common immunologically-mediated hypersensensitivity disease. It is based on the production of IgE antibodies and T cell responses against per se innocuous antigens (i.e., allergens) and subsequent allergen-induced inflammation in genetically pre-disposed individuals. While allergen exposure in sensitized subjects mainly boosts IgE production and T cell activation, successful allergen-specific immunotherapy (AIT) induces the production of allergen-specific IgG antibodies and reduces T cell activity. Under both circumstances, the resulting allergen-antibody complexes play a major role in modulating secondary allergen-specific immune responses: Allergen-IgE complexes induce mast cell and basophil activation and perpetuate allergen-specific T cell responses via presentation of allergen by allergen presenting cells to T cells, a process called IgE-facilitated antigen presentation (FAP). In addition, they may induce activation of IgE memory B cells. Allergen-induced production of specific IgGs usually exerts ameliorating effects but under certain circumstances may also contribute to exacerbation. Allergen-specific IgG antibodies induced by AIT which compete with IgE for allergen binding (i.e., blocking IgG) inhibit formation of IgE-allergen complexes and reduce activation of effector cells, B cells and indirectly T cells as FAP is prevented. Experimental data provide evidence that by binding of allergen-specific IgG to epitopes different from those recognized by IgE, allergen-specific IgG may enhance IgE-mediated activation of mast cells, basophils and allergen-specific IgE+ B cells. In this review we provide an overview about the role of allergen-specific antibodies in regulating secondary allergen-specific immune responses.